Ethical, social and political aspect of scientific researches - Gómez Navarro, Ángel (2012)
Scientific researches demand a firm link of their ethical, social and political aspect because of the axiology that theyincorporate as well as the competences that they involve. This essay reflects on this unavoidable articulation, which not onlyshapes the investigation processes but also shapes the purposes to be achieved, such as the implementation and managementof relevant knowledge that promotes sustainable development of humanity and responsible solution of the problems thataffect us as a global and pluralistic society